An interbasin comparison of tree‐ring reconstructed streamflow in the eastern United States. Issue 13 (18th May 2017) - Maxwell, R.S.; Harley, G.L.; Maxwell, J.T.; Rayback, S.A.; Pederson, N.; Cook, E.R.; Barclay, D.J.; Li, W.; Rayburn, J.A.
Abstract: Tree‐ring reconstructions of streamflow are uncommon in the eastern United States compared with the western United States. Although the east has not experienced severe drought on the scale of the west over the last 100 years, multiyear droughts have stressed the water management systems throughout the east. Here, we reconstruct mean May–September streamflow of three rivers serving population centers in the northeast (Beaver Kill River serving New York, NY), mid‐Atlantic (Potomac River serving Washington, DC), and southeast (Flint River serving Atlanta, GA) to demonstrate the efficacy of reconstructing streamflow in the eastern United States. Then, we conducted an interbasin comparison to identify periods of common variability and examined the influence of the North Atlantic subtropical high on reconstructed streamflow. Our models explained 40–61% of the variance in the instrumental record and passed verification tests in all basins during the period 1675–2000 CE. Droughts and pluvials showed some synchrony across all basins, but the mid‐Atlantic region acted as a hinge, sometimes behaving more like the northeast, and other times like the southeast. Climatic analyses suggest a relationship exists between the North Atlantic subtropical high and reconstructed streamflow that influences the probability of drought and pluvial events. Given the many factors influencing tree growth in closed‐canopy systems, we have shown that careful standardization of individual tree‐ring series, nested regression models, and the use of multiple species can produce robust proxies of streamflow across the eastern seaboard.